Early development of Betta splendens under stereomicroscopy and scanning electron microscopy - Valentin, Fernanda Nogueira [UNESP]; Nascimento, Nivaldo Ferreira do [UNESP]; Silva, Regiane Cristina da [UNESP]; Kochenborger Fernandes, Joao Batista [UNESP]; Giannecchini, Luiz Gustavo [UNESP]; Okada Nakaghi, Laura Satiko [UNESP] (Cambridge Univ Press, 2015)
Betta splendens is a very important ornamental species. The current paper describes the embryonic and larval development of B. splendens under stereomicroscopy and scanning electron microscopy. Eggs and larvae from natural spawning were collected at different developmental stages at previously established intervals and analysed. The eggs of B. splendens are yellowish, clear, spherical, demersal, translucent and telolecithal with a large amount of yolk. Between 0-2 h post-initial collection (hpIC), the eggs were at the egg cell, first cleavage and morula stages. The blastula stage was identified at 2-3 hpIC and the early gastrula phase was observed at 3-4 hpIC with 20% epiboly, which was finalized after 13-18 hpIC. When the pre-larvae were ready to hatch, the appearance of somites and the free tail were observed, at 23-25 hpIC. At 29 hpIC, the majority of larvae had already hatched at an average temperature of 28.4 +/- 0.2 degrees C. The newly hatched larvae measured 2.47 +/- 0.044 mm total length. The mouth opened at 23 h post-hatching (hPH) and the yolk sac was totally absorbed at 73 hPH. After 156 hPH, the heart was pumping blood throughout the entire larval body. The caudal fin, operculum and eyes were well developed at 264 hPH. When metamorphosis was complete at 768 hPH, the larvae became juveniles. The current study presents the first results about early development of B. splendens and provides relevant information for its reproduction, rearing and biology.
Keywords: Eggs; Embryos; Fish; Larvae; Ontogeny; Reproduction